Sleep quality and the cortisol awakening response (CAR) among law enforcement officers: The moderating role of leisure time physical activity. (September 2018) - Fekedulegn, Desta; Innes, Kim; Andrew, Michael E.; Tinney-Zara, Cathy; Charles, Luenda E.; Allison, Penelope; Violanti, John M.; Knox, Sarah S.
Highlights: Physical activity moderated association of poor sleep quality with cortisol awakening response (CAR) in police officers. In inactive officers, poor sleep quality was associated with lower morning cortisol and dampened profile during CAR period. In sufficiently active officers, poor sleep quality was not associated with morning cortisol level or CAR profile. Being sufficiently active may be protective of aberrant CAR associated with poor sleep quality. Abstract: Objective: The goal of this study was to investigate the role of leisure time physical activity (LTPA) on the association between sleep quality and the cortisol awakening response (CAR) in people with an occupation that exposes them to high levels of stress. Methods: Participants were 275 police officers (age = 42 years ± 8.3, 27% women) enrolled in the Buffalo Cardio-Metabolic Occupational Police Stress (BCOPS) study (conducted between 2004 and 2009). Officers provided four salivary cortisol samples (on awakening and 15, 30, and 45 min after awakening). Hours of leisure time physical activity were assessed using the Seven-Day Physical Activity Recall questionnaire. Sleep quality (good/poor) was evaluated using the Pittsburgh Sleep Quality Index (PSQI) scale. Analysis of covariance and repeated measures models were used to examine the association of sleep quality to the two aspects of CAR: cortisol levels (total area under the curve (AUCG ), mean, and peak cortisol) and cortisol profiles (the overall pattern in cortisol level during the 45 min period following awakening, the increase in cortisol from baseline to average of post awakening values (mean increase), and area under the curve with respect to increase (AUCI )). Analyses were stratified by participant level of reported LTPA ( sufficiently vs. insufficiently active, defined as ≥ 150 vs. < 150 min/week of moderate intensity activity, respectively). Since cortisol activity is known to be influenced by gender, we conducted additional analyses also stratified by gender. Results: Overall, results demonstrated that LTPA significantly moderated the association of sleep quality with CAR. Among participants who were sufficiently active, CAR did not differ by sleep quality. However, in those who were insufficiently active during their leisure time, poor sleep quality was associated with a significantly reduced level of total awakening cortisol secretion (AUCG (a.u.) = 777.4 ± 56 vs. 606.5 ± 45, p = 0.02; mean cortisol (nmol/l) = 16.7 ± 1.2 vs. 13.3 ± 0.9, p = 0.03; peak cortisol (nmol/l) = 24.0 ± 1.8 vs. 18.9 ± 1.5, p = 0.03 for good vs. poor sleep quality, respectively). The normal rise in cortisol after awakening was also significantly lower in inactive officers with poor sleep quality than in those with good sleep quality (mean increase (nmol/l) = 6.7 ± 1.5 vs. 2.3 ± 1.2, p = 0.03; AUCI (a.u.) = 249.3 ± 55 vs. 83.3 ± 44, p = 0.02 for those with good vs. poor sleep quality, respectively). While findings for male officers were consistent with the overall results, CAR did not differ by sleep quality in female officers regardless of LTPA level. Conclusion: Findings of this study suggest that poor sleep quality is associated with diminished awakening cortisol levels and dysregulated cortisol patterns over time, but only among officers who were inactive or insufficiently active during their leisure time. In contrast, sleep quality was not associated with any measures of CAR in officers who reported sufficient activity, suggesting a potential protective effect of LTPA. In analyses stratified by gender, findings for male officers were similar to those in the pooled sample, although we found no evidence for a modifying effect of LTPA in women. Future longitudinal studies in a larger population are needed to confirm these findings and further elucidate the relationships between LTPA, sleep quality, and cortisol response.